Ionic liquid modified PEEK-MWCNTs nanocomposites with enhanced thermomechanical properties - Ahmad, A. (IOP Publishing Ltd, 2021)
Polyetheretherketone (PEEK) is a stable semi-crystalline thermoplastic polymer with excellent thermal and chemical properties and is used in many applications, especially as a biomaterial. However, poor mechanical properties: mismatching of elastic modulus to human bone retards the use of PEEK as a biomaterial for bone implant material. In the present study, ionic liquid (IL) modified multiwalled carbon nanotubes were used to prepare PEEK nanocomposites via internal mixer and compression molding processes. The morphologies, thermal and mechanical properties of the prepared nanocomposites were evaluated. Uniform and excellent distribution of MWCNTs into PEEK was achieved by optical microscopy. The thermogravimetric study showed that the decomposition temperature of the composites was boosted 7 0.9 as compared to those of PEEK composites prepared without IL. Moreover, the elastic modulus of the PEEK nanocomposites was improved by ionic liquid modified MWCNTs into the PEEK. Thus, the prepared PEEK nanocomposites have the potential to be used for fabricating bone implants. Â© Published under licence by IOP Publishing Ltd.